Gymnosperms from the Middle Triassic of Antarctica: The First Structurally Preserved Cycad Pollen Cone - Klavins, Sharon D.; Taylor, Edith L.; Krings, Michael; Taylor, Thomas N. (International Journal of Plant Sciences, 2015)
The first permineralized cycad pollen cone is described from the lower Middle Triassic of Antarctica. The cone is characterized by helically arranged, wedge‐shaped microsporophylls, each with five or more spinelike projections extending from the rhomboid distal face. The vascular cylinder is dissected and produces paired traces to each microsporophyll. Three vascular bundles enter the base of the microsporophyll and divide to produce at least five vascular strands in the sporophyll lamina. Pollen sacs occur in two radial clusters near the lateral margins on the abaxial surface of the microsporophyll. Each cluster bears up to eight elongate pollen sacs that are fused for approximately half their length and display longitudinal dehiscence. Pollen sacs are sessile and attached to a vascularized, receptacle‐like pad of tissue that is raised from the surface of the microsporophyll. Pollen is ovoid, psilate, and monosulcate. Although the affinities of this cone with the Cycadales are obvious, the complement of characters in the fossil is unique and thus does not permit assignment to an extant family. Features of the cone are evaluated against reproductive aspects of living cycads.